Long-term analysis applied to mooring systems design - Seabra, Pedro de Amorim (2019)
This dissertation proposes a numerical/computational procedure alternative to the currently procedures used in the industry to obtain the extreme loads on offshore platforms’ mooring lines. In this context, the dissertation is based on the long-term response analysis methodology, applied to the design of conventional fixed mooring systems: FPSOs and Semi-Submersible in spread mooring configuration and turret– moored FPSOs (single point mooring). By the application of the proposed methodology, it is expected that offshore platforms’ mooring systems will be able to be designed with an appropriated reliability level for all lines – since the procedure presupposes the use of environmental data measured simultaneously, specific from the location where the Platform will be installed. The work was carried out using Dynasim software [1] to generate the time domain tension series, which were later post-processed by using computational codes developed with Python software [2]. Thus, another result of this work is the set of codes compiled specifically to perform the mooring analyses management and obtain the long-term responses based on tension time series.